Analisis Implementasi Standar Kebersihan Kamar Suite dalam Meningkatkan Kualitas Pelayanan Housekeeping di Sebuah Resor di Bali - Gresia Devita Elos; Ida Ayu Sri Puspa Adi (HeadWay Research & Developemnt, 2026)
This study aims to analyze the implementation of suite room cleanliness standards at The St. Regis Bali Resort and identify areas requiring improvement in maintaining room quality. This research employed a descriptive qualitative approach. Data were collected through direct observation of five vacant clean suite rooms, in-depth interviews with the Executive Housekeeper, and documentation. The analysis focused on seventeen cleanliness indicators established by the hotel. The findings indicate that the implementation of suite room cleanliness standards has generally been well executed, with 94% of indicators meeting the established standards. However, 6% of indicators were found to be inconsistent with the expected standards, particularly in wardrobe cleanliness, bedside furniture dusting, bathroom exhaust fan cleanliness, and balcony area maintenance. These shortcomings were primarily caused by insufficient attention to detail and time pressure experienced by room attendants during room preparation. This study concludes that while the cleanliness standards of suite rooms at The St. Regis Bali Resort are generally satisfactory, continuous supervision, routine evaluation, and enhanced staff attention to detail are necessary to ensure consistent compliance with housekeeping standards and improve guest satisfaction.